"Let Them In!" Humanitarian Work as Political Activism? The Case of the Maximiliaan Refugee Camp in Brussels. Issue 2 (3rd April 2019) - Lafaut, Dirk; Coene, Gily
ABSTRACT: Humanitarian aid projects associated with the emergence of refugee camps within European territories are generally perceived as apolitical. Scholars however, are increasingly questioning this view, pointing to many, often untold, ways in which humanitarianism interacts with the politics of migration and border enforcement. This article examines the case of a temporary refugee camp set up in Brussels in September 2015. We show how organizational and spatiotemporal particularities, as well as media framing of the humanitarian assistance, led to controversy, civil initiatives, and hyperpoliticization, eventually calling the state to take responsibility for the refugees, but simultaneously silenced other explicit political responses.